Penerapan Hasil Analisis Metode Pekerja Sosial pada Anak Rumah Yatim Medan - Lukman Nul Hakim Harahap; Muhammad Farid Anbar; Putri Gabriella Purba; Karina Olivia Pricilia Harahap; Keysha Mumtazah Silalahi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This article discusses the methods used by Rumah Yatim social workers in providing services to children in Medan Orphanage.The existence of social workers in an orphanage has a significant meaning for the process of solving problems faced by orphaned children. Social assistance is a strategy that determines the success of community empowerment. Mentoring is also an activity that means coaching, teaching, directing which connotes mastering, controlling, and controlling. The right method will be the initial stage of solving the problems complained by children and the level of efficiency of the method. Orphanage children need a social worker figure as a substitute for the role of parents who should be a place to share problems and a place to get advice as a solution to solve problems. The process of orphanage children in solving problems on their own takes quite a long time considering their immature age. The purpose of this writing is as a result of project base learning activities at the Medan Orphanage Institute. The methods used are observation and interviews in the process of collecting data related to social worker methods. Existing literature sources are also used to support the analysis of the discussion.